(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The formation of professional qualities and professional competency qualities of future teachers. The identification of a system of pedagogical conditions and means that occupy a specific place in the formation of professional qualities of the future teacher in pedagogical institutions ensures the effective and correct Organization of the educational process.